The Influence of Perceived Decision Difficulty on Online Cart Abandonment in The Apparel Industry - Aisy, Rihadathul (International Journal of Islamic Finance, 2025)
Background: Cart abandonment occurs when online shoppers add items to their virtual carts but leave the website or app before completing the purchase. This issue is particularly prevalent in the apparel industry, which has a cart abandonment rate of 77%, higher than the global average of 69.99%. This high rate poses a significant challenge to maximizing sales and customer retention, despite the industry's rapid growth. Objectives: This study aims to explore the factors contributing to the high rate of cart abandonment in the online apparel industry, with a specific focus on understanding the role of perceived decision difficulty in this phenomenon. Novelty: While previous research has addressed various aspects of online shopping behavior, this study uniquely examines how perceived decision difficulty, influenced by product attributes, consumer knowledge, maximization behavior, and physical intangibility, contributes to cart abandonment in the apparel sector. Research Methodology / Design: This quantitative study surveyed over 200 recent online apparel buyers using a purposive sampling approach. Data were collected via a structured questionnaire and analyzed using Structural Equation Modeling (SEM) to explore relationships among variables. Findings: The study found that while product attributes and consumer knowledge enhance decision-making, they do not significantly reduce perceived decision difficulty due to the complexity and cognitive effort required. Maximization behavior increases choice conflicts but does not directly impact decision difficulty. Physical intangibility, or the inability to examine apparel in person, exacerbates decision difficulty and increases uncertainty. High perceived decision difficulty, driven by choice conflicts and physical intangibility, is a significant factor contributing to cart abandonment. Implication: Enhancing product information and introducing decision support tools like virtual fitting rooms could reduce decision difficulty and lower cart abandonment rates.